Frequency of hepatitis D virus with different hepatitis B virus serological markers and coinfections in hospital patients from Argentina: synchronous testing of anti-HDV antibodies and HDV RNA - Giorgio, Marianela; Ramírez Ladino, Kelly Alejandra; López, Guido; Sosa Rojas, Maricel; Outon, Estela; Delfino, Cecilia María (European journal of gastroenterology & hepatology, 2025)
Hepatitis D virus (HDV) RNA-positive cases with total anti-HDV antibodies nonreactive were documented. Moreover, HDV infection was observed in subjects with occult hepatitis B virus infection. The prevalence of HDV infection in Argentina is low; however, further research in different populations is needed. This study aimed to perform synchronous HDV detection in reactive hepatitis B virus patients treated in a public hospital in the province of Buenos Aires, Argentina, some of whom were coinfected with hepatitis C virus and/or HIV. A total of 189 hepatitis B virus-reactive serum samples with or without hepatitis C virus and/or HIV coinfection were synchronously analyzed for anti-HDV antibodies and HDV RNA. HDV prevalence was 4.2% with HDV RNA found in 61 samples, most of which were nonreactive to anti-HDV antibodies and hepatitis B surface antigen. Genotype 1 was identified in all HDV sequences. Moreover, triple and quadruple infections were observed, showing a high frequency of HDV infection in hospitalized patients not following the recommended diagnostic algorithm. This study is evidence that the synchronous testing of anti-HDV antibodies and HDV RNA is necessary for the diagnosis of HDV infection in Argentina. Finally, further research is necessary to identify high-risk populations and improve prevention and control strategies for triple and quadruple infections and their potential consequences.